Populism and Foreign Policy: The Case of India. Issue 2 (3rd December 2018) - Plagemann, Johannes; Destradi, Sandra
Abstract: What kind of foreign policy do populists execute once in power? Based on the existing literature, we conceptualize populism as a set of ideas whose two core elements are anti-elitism and antipluralism. From this we develop a set of hypotheses regarding both substantive aspects of foreign policy as well as foreign policy–making processes of populist leaders in government. An analysis of Indian Prime Minister Narendra Modi's foreign policy record serves as a first plausibility probe of our hypotheses. We find that our concept of populism carries most explanatory value in the procedural aspects of foreign policy making as well as in its communication, less so in those aspects relating to the goals or substance of foreign policy. Whereas foreign policy under Modi's populist leadership is highly centralized and personalized, the traditional foreign policy establishment, including most notably the Ministry of External Affairs, has lost some of its previous authority. Engaging the Indian diaspora abroad emerged as another characteristic of populist foreign policy making. By contrast, the case of India does not confirm our hypothesis regarding a preference of bilateralism over multilateralism, nor does populism necessarily preclude investing in global public goods. Video Abstract: